DETERMINANTS OF MUTUAL FUNDS INVESTMENT BEHAVIOR - Marcella Julia Shira; Werner Ria Murhadi; Bertha Silvia Sutejo (Manajemen dan Bisnis, 2017)
The purpose of this study is to examine the effects of demographic and social characteristics, investment criteria, perceptions and investors awareness of investment behavior on mutual funds in Indonesia. Analysis in this research using logistic regression or logit regression. The object of this study is investors and non-investors of mutual funds in Indonesia, as many as 126 people. Data processing uses SPSS PASW software version 18 for the Windows operating system. The results of this study show that demographic and social characteristics, investment criteria, and awareness of investors simultaneously have a significant effect on investment behavior on mutual funds in Indonesia.